2016
DOI: 10.7589/2015-04-103
|View full text |Cite
|
Sign up to set email alerts
|

EYEWORMS (OXYSPIRURA PETROWI) IN NORTHERN BOBWHITES (COLINUS VIRGINIANUS) FROM THE ROLLING PLAINS ECOREGION OF TEXAS AND OKLAHOMA, 2011−13

Abstract: The Northern Bobwhite ( Colinus virginianus ) has been steadily declining throughout much of its historic range for decades. The Rolling Plains ecoregion of Texas and western Oklahoma, historically rich with wild Northern Bobwhites and one of the last remaining quail strongholds, also has a declining population. During August and October in 2011-13, 348 Northern Bobwhites from the Rolling Plains were examined for eyeworms (Oxyspirura petrowi). Of these 348 Northern Bobwhites, 144 (41.4%) were infected with 1,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…Recently, a parasitic eyeworm ( Oxyspirura petrowi ) has received increased attention due to the high prevalence detected in native galliforme populations in the United States ( Robel et al., 2003 , Villarreal et al., 2012 , Dunham et al., 2016 ). Specifically, the decline of the Northern bobwhite ( Colinus virginianus ) in west Texas has prompted an investigation of the factors influencing the disappearance of these birds.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a parasitic eyeworm ( Oxyspirura petrowi ) has received increased attention due to the high prevalence detected in native galliforme populations in the United States ( Robel et al., 2003 , Villarreal et al., 2012 , Dunham et al., 2016 ). Specifically, the decline of the Northern bobwhite ( Colinus virginianus ) in west Texas has prompted an investigation of the factors influencing the disappearance of these birds.…”
Section: Introductionmentioning
confidence: 99%
“…Helminth parasites have been overlooked historically ( Lehman, 1984 ), but eyeworm infections are now considered a possible factor contributing to the decline of Northern bobwhites in Texas ( Dunham et al., 2014 , Dunham et al., 2016 , Bruno et al., 2015 ). Oxyspiurura petrowi is a heteroxenous parasitic nematode reported to infect the eyes of many avian hosts ( Dunham and Kendall, 2016 ) with species of this genus being documented in >80 avian species worldwide ( Addison and Anderson, 1969 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…pennula and O . petrowi to be ubiquitous in quail throughout the region ( Dunham et al, 2016a ; Olsen and Fedynich, 2016 ). In subsequent studies, Bruno et al (2019b) found 40% of bobwhite sampled from 2011 to 2013 to be infected with O .…”
Section: Using the Woe Framework To Investigate The Role Of Parasitesmentioning
confidence: 99%
“…During this study, 348 northern bobwhites were screened for different pathogens. Infection rates of 41.4% of bobwhite collected from individual sites in the Rolling Plains ecoregion by the parasitic nematode eyeworm Oxyspirura petrowi (Spirurida:Thelaziidae) was reported (Dunham et al 2016 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%